An extension of first order limit language - Muhammad Azrin, Ahmad; Nor Haniza, Sarmin; Heng, Fong Wan; Yuhani, Yusof (AIP Publishing LLC., 2014)
The study on cutting and pasting of DNA molecules under the framework of Formal Language Theory has led to the mathematical modelling of splicing system. The output of splicing system is the splicing language which can be categorized into three types: adult or inert persistent, transient and limit language. In the biological point of view, limit language is predicted to appear after the reaction of DNA molecules and enzyme with the existence of appropriate ligase reached the equilibrium state. In this research, the second order limit language is investigated. It is defined as the distinct language after splicing occurs among the resulting splicing language of the first order splicing language. Besides that, the characteristics of second order limit language are observed based on the properties of the crossing sites of the rules such as left or right context and palindromic via Y-G approach. The results lead to some examples and theorems which are presented in this paper.